2021
DOI: 10.3390/molecules26010208
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin’s Anti-Quorum Sensing Activity Can Be Enhanced When Combined with Other Plant-Derived Small Molecules

Abstract: Coumarins are class of natural aromatic compounds based on benzopyrones (2H-1-benzopyran-2-ones). They are identified as secondary metabolites in about 150 different plant species. The ability of coumarins to inhibit cell-to-cell communication in bacterial communities (quorum sensing; QS) has been previously described. Coumarin and its derivatives in plant extracts are often found together with other small molecules that show anti-QS properties too. The aim of this study was to find the most effective combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…In the previous studies, a group of inhibitors of “quorum sensing” – plant metabolites used in this experiment – was identified [ 27 ], their toxicity was evaluated [ 28 ], and effective combinations were determined [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the previous studies, a group of inhibitors of “quorum sensing” – plant metabolites used in this experiment – was identified [ 27 ], their toxicity was evaluated [ 28 ], and effective combinations were determined [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Azoles, including pyrazoles, oxadiazoles, and triazoles, have been extensively studied as antifungal agents, but recent studies have shown that they also have antibacterial activity against resistant strains [ 17 ]. Coumarins have been found to inhibit bacterial quorum sensing and motility [ 18 ], while indoles and thiophenes have also shown potential as quorum sensing inhibitors [ 19 ]. Quinolines have been proposed as inhibitors of bacterial type II topoisomerases and have shown activity against multidrug-resistant bacteria [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results have been achieved by getting the sequence of amino acids from the NCBI databases in FASTA format. Therefore, the in silico methods have made it possible to discover, in various microorganisms, an endless number of QS inhibitory molecules, such as different aromatic compounds, for instance, tyrosol halogenated furanone, coumarins, flavones, and their derivatives [17] , [18] , [19] , [20] , [21] , [22] , [23] . Molecular docking software is currently used for validation by docking and re-docking protocols, either as licensed or free software (e.g., Autodock vina, Autodock4, LeDock, GOLD, Chimera, Mcule, and PyRx) [ 21 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This information serves to create point mutations in the QS transcriptional regulators to understand the biological role of amino acids in the protein-ligand binding. Likewise, gene cloning is related to the synthesis of new molecules and increases the affinity to the autoinducer-1 binding domain in the transcriptional regulator of QS obtained, thus attenuating bacterial virulence regulated by QS [19] .…”
Section: Introductionmentioning
confidence: 99%